SOSIALISASI SAMPAH ORGANIK DAN NON ORGANIK SERTA PELATIHAN KREASI SAMPAH - Agus Taufiq (Asian Journal of Innovation and Entrepreneurship, 2015)
Dusun Klumprit II is a dusun that located in Wukirharjo, Prambanan, District Sleman, Province of Yogyakarta. Dusun Klumprit II is a prosperous dusun with themajority of livelihoods are in agricultural and livestock. The residents’ awareness andconcern to manage the waste by the residents is still very low. The habit of burning thewaste is still ingrained in the dusun to solve the waste problem. Besides, with burningthe waste is considered as the fastest way to handle these problems. Not only that,there are some residents who throw their waste directly into the water bodies withoutthinking about the accumulation of the waste in the downstream water bodies and alsopollution in water body as a result of the waste that they has thrown. It is feared that itwill be imitated by the children of dusun as the successor of the dusun and also fearedthat the environmental carrying capacity will be weakened due to contamination thatoccurred. Such concerns can be reduced by growing the public awareness of theimportance of removing and sorting the waste.The result of the program, the residents begin to understand the importance ofmanaging the waste. Instead it will help to preserve the environment but it can also helpthe economy of the residents with the training of the creations that can be made fromthe waste. As well as the control approaches the waste to children through the activityof making crafts from the waste by their own efforts and hopes their creativity in thefuture can be honed to solve the waste problems and the cadres that cares intoenvironments is born. With the procurement of the trash can, the residents can do thereal actions in the management of waste by sorting both organic and non-organic.